Why I Joined Facebook and Still Regret It. (29th April 2015) - Jordan, Tim
This article argues for a particular understanding of identity and sociality in social media. While there is considerable insightful research about the sociality and subjectivity produced in social media, it is also important to see that such identity and sociality is about creating and maintaining public-private boundaries online that can be different to those divisions of public and private that are lived offline.